INTEGRATING DIETARY EDUCATION: STARFRUIT JUICE ON BLOOD PRESSURE IN WOMEN USING INJECTABLE CONTRACEPTIVES - Quds Alifah Qatrunada; Tut Rayani; Rifzul Maulina (CV. TOTUS TUUS, 2025)
The rising prevalence of hypertension among women using three-month injectable contraceptives highlights a fundamental need for safe, effective, and accessible blood pressure management strategies in reproductive health care. This study aimed to evaluate the antihypertensive effect of starfruit (Averrhoa carambola L.) juice among women receiving injectable contraception at PMB Siti Fatimah, Bandungrejosari, Malang. Utilizing a quasi-experimental one-group pretest-posttest design, twenty eligible participants consumed 100 ml of starfruit juice daily for seven days. Blood pressure was measured before and after the intervention using standardized instruments. Results showed a significant reduction in both systolic and diastolic blood pressure in the intervention group (mean reduction: 10/11.11 mmHg), with 77.8% of participants experiencing notable decreases (Wilcoxon p < 0.05), compared to only modest changes in the control group. These findings suggest that regular starfruit juice intake is an effective, natural, non-pharmacological option for managing hypertension, particularly among women at higher risk due to contraceptive use. This research contributes new evidence supporting the integration of dietary and complementary therapies into midwifery education and practice. The results advocate for nutrition counseling as part of family planning services, emphasizing holistic and preventive care. For future research, studies with larger, more diverse samples and longer follow-up periods are recommended to confirm and generalize these findings.